A Morphosyntactic and Lexical Error Analysis in English SOP Writing on Welding Procedures by Mechanical Engineering Students - Ahsin Fahmi Mubarok; Setiyo Rojikin; Mochammad Abdullah Salim (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2026)
This research examines the most common morphological and lexical errors in English Standard Operating Procedures (SOPs) for welding machines authored by Indonesian mechanical engineering students. Using a descriptive qualitative method, ten student-generated SOPs on Shielded Metal Arc Welding (SMAW) were analyzed. The study found that most errors arose from negative transfer from Indonesian, a language with minimal obligatory inflectional and derivational morphology. The top three morphological mistakes were the omission of the adverbial suffix -ly (8 occurrences), the omission of the plural -s (6 occurrences), and the omission of nominal suffixes (6 occurrences). Lexical errors were also prevalent, particularly inaccurate collocations (e.g., do welding instead of perform welding) and incorrect phrasal verbs, reflecting a tendency to translate literally rather than use established English technical expressions. These errors undermine the clarity, precision, and safety essential for effective SOPs. The results suggest the need for focused instructional strategies that contrast English morphological and idiomatic conventions with Indonesian to enhance students’ accuracy in technical English writing.